The impact of psychological factors on consumer buying behavior and an empirical application in Turkey - Durmaz Y. (My University, 2014)
In this study, the influence of psychological factors on consumer buying behavior is investigated. The effect of psychological factors on buying behavior of consumers, who become much more important day by day, is tried to be measured. Turkey has seven regions. From each region two provinces are selected by random sampling method. A face to face survey was conducted on 100 people from each province and in total 1400 people participated in the survey. The information obtained from the results are analyzed and interpreted by the computer packet programs.
Keywords: Beliefs and attitudes; Consumer; Learning; Motivation; Perception; Psychological factors